Financial Sustainability and Value of Joint-Stock Companies from Food Industry in Central and Eastern Europe - Serhiy Zabolotnyy; Natalia Wasilewska; Mirosław Wasilewski (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The research presents the analysis of relations between financial sustainability and value of joint-stock companies from food industry in Central and Eastern Europe. Increase of volume of assets, shareholders’ equity and revenues demonstrated an improvement of financial sustainability and resulted in growing valuations of companies in the study period. Sample business entities achieved relatively high liquidity and profitability that proved their financial sustainability in terms of risk and return. At the same time rising operating profit margins and liquidity ratios determined higher enterprise value of joint-stock companies. This emphasized a positive relation between enterprise value and financial sustainability. Joint-stock companies demonstrated a robust capital structure with a minor decrease of corporate debt in 2011-2015. However changes in sources of financing could provoke a trade-off between financial sustainability and enterprise value. According to a regression model factors positively influencing enterprise value included revenue, cash and cash equivalents, operating profit, current liabilities and shareholder’s equity. Stimulating revenue and increasing operating profit as well as maintaining higher cash balances improves financial sustainability while debt extension can significantly deteriorate continuity of business.